2010
DOI: 10.1111/j.1440-1827.2010.02608.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal thrombotic microangiopathy associated with chronic humoral graft versus host disease after hematopoietic stem cell transplantation

Abstract: Thrombotic microangiopathy (TMA) is a known complication of hematopoietic stem cell transplantation (HSCT). The pathogenesis of TMA is controversial but considered to involve various factors such as total body irradiation, use of calcineurin inhibitors for prophylaxis against graft versus host disease (GVHD), viral infection, and GVHD. Herein we describe a case with renal TMA after HSCT, which was probably associated with antibody-mediated endothelial cell injury from chronic GVHD (termed here 'chronic humoral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Mii et al 23,49 surmised that this finding might provide evidence of antibodymediated pathology, based on analogy with antibody mediation rejection in solid organ transplantation. 49 Subsequently, Laskin et al 25 found arteriolar but not glomerular C4d staining to correlate with histologic thrombotic microangiopathy in patients with both allogeneic and autologous hematopoietic cell transplant. However, neither study included a nonhematopoietic cell transplant thrombotic microangiopathy control group.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Mii et al 23,49 surmised that this finding might provide evidence of antibodymediated pathology, based on analogy with antibody mediation rejection in solid organ transplantation. 49 Subsequently, Laskin et al 25 found arteriolar but not glomerular C4d staining to correlate with histologic thrombotic microangiopathy in patients with both allogeneic and autologous hematopoietic cell transplant. However, neither study included a nonhematopoietic cell transplant thrombotic microangiopathy control group.…”
Section: Discussionmentioning
confidence: 97%
“…In separate studies, Mii et al, 23,49 Laskin et al, 25 and Sakamoto et al 50 demonstrated C4d labeling in arterioles and glomeruli of biopsy and autopsy kidney specimens from patients with hematopoietic cell transplant and thrombotic microangiopathy. Mii et al 23,49 surmised that this finding might provide evidence of antibodymediated pathology, based on analogy with antibody mediation rejection in solid organ transplantation. 49 Subsequently, Laskin et al 25 found arteriolar but not glomerular C4d staining to correlate with histologic thrombotic microangiopathy in patients with both allogeneic and autologous hematopoietic cell transplant.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…50 Recently, the first case that documented TA-TMA secondary to Ab-mediated tissue injury showed by diffuse C4d deposition in the glomerular capillaries was published. 40 Because detection of C4d is a reliable marker of Ab deposition and complement activation, 49 the investigators concluded that this case of TA-TMA was probably mediated by a humoral immune response. However, no circulating anti-HLA Abs were detected.…”
Section: Complementmentioning
confidence: 96%
“…35 Smaller studies have identified elevated levels of circulating cytokines, including IL-8, IL-12, and thrombomodulin, during TA-TMA. 21,40,41 The variable antigenicity of endothelial cells may explain why certain patient populations are more resistant to cytokine-induced vascular injury than others. 35 …”
Section: Gvhd and Cytokinesmentioning
confidence: 99%